EIB Working Paper 2022/01 Firm-level policy support during the crisis - European Investment Bank (European Investment Bank, 2022)
During the COVID-19 crisis, the European corporate ecosystem avoided major disruptions, and corporate bankruptcy rates even declined. This outcome mostly resulted from the strength of support from monetary, financial supervisory and fiscal policies. Using the 2021 vintage of the EIB Investment Survey (EIBIS) matched with balance sheet data on firms' profits and losses, this paper investigates what has driven the allocation of fiscal policy support and the impact of this support during the investment recovery. It finds that support was largely directed towards firms that were most affected by the crisis in terms of lost sales, and was not tilted firms already weak before the crisis. It also shows that the firms that benefitted from this support tend to be more optimistic in their investment plans, especially with regard to digital technologies.